One hundred priority questions for landscape restoration in Europe. (May 2018) - Ockendon, Nancy; Thomas, David H.L.; Cortina, Jordi; Adams, William M.; Aykroyd, Toby; Barov, Boris; Boitani, Luigi; Bonn, Aletta; Branquinho, Cristina; Brombacher, Michael; Burrell, Charles; Carver, Steve; et al.
Abstract: We present the results of a process to attempt to identify 100 questions that, if answered, would make a substantial difference to terrestrial and marine landscape restoration in Europe. Representatives from a wide range of European governmental and non-governmental conservation organisations, universities, independent ecologists and land managers compiled 677 questions relating to all aspects of European landscape restoration for nature and people. The questions were shortlisted by an email vote, followed by a two-day workshop, to produce the final list of 100 questions. Many of the final questions evolved through a process of modification and combination as the workshop progressed. The questions are divided into eight sections: conservation of biodiversity; connectivity, migration and translocations; delivering and evaluating restoration; natural processes; ecosystem services; social and cultural aspects of restoration; policy and governance; and economics. We anticipate that these questions will help identify new directions for researchers and policy-makers and assist funders and programme managers in allocating funds and planning projects, resulting in improved understanding and implementation of landscape-scale ecological restoration in Europe. Highlights: We identify 100 questions that, if answered, would enhance ecological restoration. Questions cover all aspects of landscape restoration in Europe. A wide range of restoration experts identified questions by voting and discussion. We hope these will be used by policy-makers, funders and researchers.